Economic Diplomacy and Its Impact on Nepalese Economy - Kharel, Khom Raj; Upadhayaya, Yadav Mani (Management Dynamics, 2021)
Economic diplomacy is concerned with how a government maintains economic relations with other nations and what steps it might take to enhance its economy. If economic and diplomatic relations are good, more benefits can be reaped from diplomatic partner countries. Economic diplomacy plays an important role in a country’s ability to prioritize and benefit from deployment partners. By developing economic diplomatic connections, Nepal has the opportunity to profit from the neighboring countries. Despite the differences in the ideology and vision of political parties, it is necessary for the country, the people and development to rise above partisan vision and move forward with a new vision. Reaching more economic benefits from respectable and balanced economic diplomacy has become imperative. This study has been conducted to review economic diplomacy and examine the impact of economic diplomatic relations on foreign direct investment, foreign employment, and the tourism economy. It measured the impact of economic diplomatic relations on FDI, foreign employment and the tourism economy by applying multiple regression models. The impact of FDI, foreign employment and the tourism economy has been analyzed from 2001 to 2019. The study’s finding shows that there has been a significant impact on remittance income and incomes from the tourism industry.